2016
DOI: 10.2215/cjn.13111215
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Kidney Disease, and Cardiovascular Outcomes in the Jackson Heart Study

Abstract: Background and objectives Blacks have high rates of cardiovascular disease and mortality. Diabetes and CKD, risk factors for cardiovascular mortality in the general population, are common among blacks. We sought to assess their contribution to cardiovascular disease and mortality in blacks.Design, setting, participants, & measurements This observational cohort study was of 3211 participants in the Jackson Heart Study (enrolled 2000-2004). Rates of incident stroke, incident coronary heart disease, and cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Not surprisingly, the KNOW-CKD study showed that diabetic patients were at a high risk for CVD, as previously reported in other cohort studies (101524). With the rapid transition to a Westernized lifestyle, the prevalence of diabetes has increased during the last decades in Korea, and about 10% of persons without CKD aged ≥ 30 years had diabetes (25).…”
Section: Discussionsupporting
confidence: 81%
“…Not surprisingly, the KNOW-CKD study showed that diabetic patients were at a high risk for CVD, as previously reported in other cohort studies (101524). With the rapid transition to a Westernized lifestyle, the prevalence of diabetes has increased during the last decades in Korea, and about 10% of persons without CKD aged ≥ 30 years had diabetes (25).…”
Section: Discussionsupporting
confidence: 81%
“…After the onset of proteinuria, median survival is only about seven years, and this increased mortality is mainly due to cardiovascular death rather than renal failure (34). High levels of serum creatinine and reduced eGFR have also been demonstrated to be indicative of progressive cardiovascular disease among diabetic patients (35,36), and increased levels of cystatin C have been associated with the development of cardiovascular events (37)(38)(39)(40). Some authors have even shown that cystatin C is a stronger predictor of cardiovascular outcomes in patients with diabetes and elderly adults than creatinine and eGFR (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of patients with diabetes develop DN characterized by an increase in albuminuria and blood pressure, and a declining kidney function progressing to end stage renal disease [2]. Even mild degrees of albuminuria and a decrease in the glomerular filtration rate are associated with significantly increased risks of developing cardiovascular disease, end-stage renal disease, and/or premature mortality [3][4][5]. Microalbuminuria (MA) (urinary albumin excretion 30-299 mg/24 h or 30-299 mg albumin/g creatinine) is an independent predictor of overt nephropathy, loss of renal function and incidence of cardiovascular disease in patients with diabetes 2.…”
Section: Introductionmentioning
confidence: 99%